2016
DOI: 10.1016/j.carbon.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in the mechanical properties of Gilsocarbon

Abstract: The objective of this study is to investigate whether there is significant spatial variability in the mechanical properties of Gilsocarbon nuclear graphite at different sections of the billet; specifically the dynamic Poisson's ratio, dynamic shear modulus, dynamic Young's modulus and density. Similar studies have been done, usually in the context of manufacturing, to assess the quality of graphite components for nuclear reactors. In this new study, the measurements have been carried out at a much higher spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In general, these random fields present similar patterns as the ones found in Figure 15. This resemblance is expected because of the relationship between density and Young's modulus values [32,38]: graphite denser areas tend to be stiffer. This fact Figure 17e to Figure 17h.…”
Section: Gilsocarbon Young's Modulusmentioning
confidence: 90%
See 3 more Smart Citations
“…In general, these random fields present similar patterns as the ones found in Figure 15. This resemblance is expected because of the relationship between density and Young's modulus values [32,38]: graphite denser areas tend to be stiffer. This fact Figure 17e to Figure 17h.…”
Section: Gilsocarbon Young's Modulusmentioning
confidence: 90%
“…(The complete data set can be found in reference [32].) A subset of 328 samples were used for the calculations of this research and the locations of these samples are shown in Figure 2 The summary of the density and Young's modulus values for Gilsocarbon are divided in Table 1 and Table 2.…”
Section: Gilsocarbon Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Around half of this is an open network of gas evolution and escape pores covering multiple scale-lengths (nm-to-mm), while the other half are closed pore features, specifically micro/nano-sized cracks that form due to the anisotropic contraction of crystallites during cooling after graphitisation at 2800-3000ºC [2][3][4]. Such a large and varied flaw population is heterogeneously distributed throughout the microstructure of Gilsocarbon, causing its density to display significant spatial variability [5]. This translates into slightly anisotropic (near-isotropic) properties, substantial spread in property measurements, and significant specimen size effects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%